Litterære marginalier i Svendborg-antifonalet fra 1413: Fragmenter af en dyrefabel og to Låle-ordsprog - Lerche Nielsen, Michael; Troelsgård, Christian (Danske Studier, 2024)
The parchment fragment F34 in the Provincial Archives of Fyn (Odense) is a damaged bifolium from a fully notated antiphoner, carefully written by the friar Johannes Nielssøn in 1413 and destined for the Church of Our Lady in Svendborg, as revealed by a colophon preserved at the bottom of the second verso page. No other fragments of the ‘Svendborg Antiphoner’ have until now been identified. The present paper focuses on three hitherto unremarked literary annotations in the lower margins, all written in Nielssøn’s hand. The first one is the opening hexameter of the last elegiac couplet from a medieval versification of an Aesopian fable about a stag hiding in a barn (‘De cervo et bove’, Hervieux II, 58): Exulis est non esse suum, vigilare potentis, / [Stertere servorum, velle iuvare pii], representing the moral of the fable: »Nobody is safe when far from home (i.e. the stag), a master is vigilant (i.e. the farmer who finds the stag), servants are snoring (i.e. the farmhands do not notice what is happening), the pious one wants to help (i.e. the cow which tries to hide the stag in the barn)«. The two remaining annotations record the opening words of two Latin hexameter proverbs, known from the medieval collection of Latin-Danish pairs of proverbs attributed to Peder Låle: a) Stuppeus [est palpo de post holosericus ante] »A sycophant shows a silky façade, while his rear is coarse as hemp«, and b) Sus nigra per [tesqua noctu vix ducitur atra], »It is difficult to lead a black sow through the dark wilderness at night«. These annotations most probably reflect text types used for teaching Latin in the schools of late medieval Scandinavia; similar texts are pointed out in other manuscripts, a number of which are linked to Franciscan convents in Denmark and Scandinavia. Being the earliest precisely dated witness of the Låle collection, which is documented only in a few other manuscripts of the fifteenth century and three early prints from the beginning of the sixteenth, the annotations add important information about the transmission of the collection, its use, and the relationship between the Latin and the vernacular versions of the proverbs.